2019
DOI: 10.3389/fphys.2019.01227
|View full text |Cite
|
Sign up to set email alerts
|

Anti-oxidant and Anti-inflammatory Effects of Aquatic Exercise in Allergic Airway Inflammation in Mice

Abstract: Oxidative stress and inflammation are key pathways responsible for the pathogenesis of asthma. Aquatic exercise (AE) has been proven to elicit a variety of biological activities such as anti-oxidant and anti-inflammatory effects. However, although proper forms of AE provide beneficial health effects, incorrect forms and types of AE are potentially injurious to health. Several studies have investigated AE, but the relationship between types of AE and asthma has not been fully elucidated. This study evaluated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…Our data showed that proinflammatory factors such as IL-6 and TNF-α were significantly increased in the PI group compared to the CON group, but exercise ameliorated its expression. Similar results from previous studies and current studies suggest that aerobic exercise has a protective role in decreasing the inflammatory response in the lungs (Gonçalves et al, 2012;Vieira et al, 2012;Cardoso et al, 2018;Lee et al, 2019). Recent studies have shown that exposure to PM affects respiratory frequency, the number of breaths, and breathing volume (Brown et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…Our data showed that proinflammatory factors such as IL-6 and TNF-α were significantly increased in the PI group compared to the CON group, but exercise ameliorated its expression. Similar results from previous studies and current studies suggest that aerobic exercise has a protective role in decreasing the inflammatory response in the lungs (Gonçalves et al, 2012;Vieira et al, 2012;Cardoso et al, 2018;Lee et al, 2019). Recent studies have shown that exposure to PM affects respiratory frequency, the number of breaths, and breathing volume (Brown et al, 2013).…”
Section: Discussionsupporting
confidence: 89%
“…Western blotting was performed as described previously ( 25 ). The cytosolic and nuclear fraction preparation was performed using ExKine™ Nuclear and Cytoplasmic Protein Extraction Kit (Abbkine, China) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…All mice were randomly divided into five groups ( n = 5~10) as follows: sham control (CTL, n = 10), OVA ( n = 10), OVA + low dose of FAGS (LFAGS; 300 mg/kg/day, n = 5), OVA + high dose of FAGS (HFAGS; 600 mg/kg/day, n = 10), and OVA + CK (50 μM/kg/day, n = 5). The protocol for the induction and treatment of allergic asthma was modified based on a previous study [ 28 ]. On days 0, 7, and 14, 100 µg of OVA (Hyglos GmbH, Regensburg, Germany) dissolved in 200 μL of phosphate-buffered saline (PBS) with 2 mg of aluminum hydroxide (alum; Invivo Gen, SanDiego, CA, USA) was intraperitoneally injected into each mouse for sensitization.…”
Section: Methodsmentioning
confidence: 99%
“…The increase in pulmonary resistance upon challenge with aerosolized MCh in awake mice was assessed to determine the degree of airway hyperresponsiveness using a whole-body plethysmograph (OCP 3000; Allmedicus, Gyeonggi, Korea) as previously described [ 28 ]. Briefly, mice were exposed to 25 and 50 mg/mL of MCh (Sigma) for 10 min using a nebulizer (HARVARD73-1963; Harvard Apparatus, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation